THE INDIA–WORLD BANK: HISTORICAL RELATIONSHIP - R. Venkatesh (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Abstract Cooperation between the World Bank and India goes back to the foundation of the International Bank for Reconstruction and Development (IBRD) in 1944. As one of 44 countries, India prepared the agenda for the Bretton Woods Conference in June 1944. The Indian delegation led by Sir Jeremy Raisman, Finance Member of the Government of India, proposed the name "International Bank for Reconstruction and Development India managed to lift 133 million people out of poverty between 1994 and 2012. However, India with a population of 1.3 billion shows 5% of its population living in extreme poverty. In June 2018, India ran a current account deficit of USD 15.8 billion, marking the highest deficit in the last five years. India exported USD 261 billion in 2016, making it the 17th largest exporter in the world. However, India's export structure is still not really diversified and focuses primarily on commodities and primary products. Diamonds and jewelry and packaged pharmaceuticals account for about 20% of the export sector